The choice of the optimal experimental model of myocardial infarction - Koval’skaja, V. V.; Savytskyi, I. V.; Mironov, A. A. (Journal of Education, Health and Sport, 2017)
Nowadays myocardial infarction has a high percentage of mortality [12], and is widespread inUkraine and Western countries [1, 2, 3]. Such a situation calls for the development of a new model of myocardial infarction, which would be as simple and effective as possible. In this article, a model of myocardial infarction with the use of inhalation anesthesia with chloroform is proposed.